2021
DOI: 10.1108/bfj-11-2020-1054
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' preferences for intrinsic and extrinsic product attributes of plant-based eggs: an exploratory study in the United Kingdom and Italy

Abstract: PurposePlant-based eggs have recently been developed to provide consumers with a healthier, animal-friendlier and more sustainable alternative to conventional eggs. The purpose of this paper is to investigate intrinsic and extrinsic attribute preferences for three prototypes of plant-based egg, namely the liquid, powder and egg-shaped.Design/methodology/approachNine focus groups in the United Kingdom and nine in Italy were conducted, with a total of 180 participants. A thematic analysis of results was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Although some will choose to reduce meat in their diet for financial reasons (De Boer et al, 2017), research has identified that consumers often associate meat alternatives with being expensive or less value for money than meat (Bryant, 2019;Peschel et al, 2019). Although certain PBPs are perceived as more expensive than meat and dairy equivalents (Ellmore, 2020;Finder, 2019;Michel et al, 2021;Rondoni et al, 2021), it has been suggested that as availability of PBPs becomes more widespread, and scale of production increases, the price of these products may correspondingly decrease (Bryant, 2019) thereby reducing or removing this barrier to consumption for consumers. There can be some ambiguity among consumers regarding new product categories and how much they should cost (Lowe & Alpert, 2010); therefore, it is important that manufacturers and marketers communicate the value of their product to consumers, emphasizing known product attributes which are important to consumers.…”
Section: Product Attributesmentioning
confidence: 99%
“…Although some will choose to reduce meat in their diet for financial reasons (De Boer et al, 2017), research has identified that consumers often associate meat alternatives with being expensive or less value for money than meat (Bryant, 2019;Peschel et al, 2019). Although certain PBPs are perceived as more expensive than meat and dairy equivalents (Ellmore, 2020;Finder, 2019;Michel et al, 2021;Rondoni et al, 2021), it has been suggested that as availability of PBPs becomes more widespread, and scale of production increases, the price of these products may correspondingly decrease (Bryant, 2019) thereby reducing or removing this barrier to consumption for consumers. There can be some ambiguity among consumers regarding new product categories and how much they should cost (Lowe & Alpert, 2010); therefore, it is important that manufacturers and marketers communicate the value of their product to consumers, emphasizing known product attributes which are important to consumers.…”
Section: Product Attributesmentioning
confidence: 99%
“…In addition to playing an important role in the assessment of product quality, extrinsic cues are also features that significantly influence consumer decision-making, and help the assessment of the expected performance, safety, and social acceptance of the product [39], and their role is also important when examining perceived healthiness as well [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Third, we explored challenges in terms of product development, marketing, and policy regulations for plant-based eggs by interviewing startup businesses and researchers. In terms of R&D and production, the main problem is related to the difficulties for plant-based eggs to replicate the functionalities and taste of conventional eggs, which could limit their appeal as corroborated by Rondoni, Millan & Asioli (2021). This finding is corroborated by previous studies on plant-based meat, which revealed that poor taste and texture still act as major barriers for consumers' acceptance for plant-based foods (Cliceri, Spinelli, Dinnella, Prescott, & Monteleone, 2018), particularly among people who are not vegan or vegetarian and consume plant-based meat alternatives never or rarely (Hoek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(The Good Food Institute, 2018). In the last few years, several prototypes of plant-based eggs have been developed in different countries, including the United States, Brazil, and Italy, from both startup businesses and research centers (Rondoni, Millan & Asioli, 2021). For instance, examples of liquid plant-based eggs produced through a process of protein isolation and sold in bottles are already available to consumers in the US market (Watson & Shoup, 2019).…”
Section: Introductionmentioning
confidence: 99%